Leadership in network marketing : exploring the perspectives of leaders in network marketing companies : a thesis presented in partial fulfilment of the requirements of the degree of Master in Management at Massey University, Auckland, New Zealand - Trajanovska, Andrijana (Massey University, 2013)
This thesis is an exploratory study of leadership in the network marketing industry from the perspective of leaders themselves. There is no intention to create a new leadership theory; this thesis simply explores leadership in an industry rapidly increasing in both volume and significance, but thus far neglected in leadership scholarship. Thematic analysis within a social constructionist theoretical framework is used as a tool to analyse the data collected from semi-structured interviews with nine research participants representing five network marketing companies operating both in New Zealand and internationally. These participants have been leading teams of salespeople for a number of years in one or more network marketing companies. The interviewees were asked to discuss their experiences as either a past or current leader in their company. The analysis of the interviews focused on how leadership is realised in the leaders’ relationships with their followers (team members), peers and mentors. The findings are that: firstly, leaders in network marketing believe that leadership can be learned; and they view their role as a provider of technical support rather than of motivation (nature of leadership in network marketing). Secondly, leaders start their career in network marketing with materialistic reasons as their primary motivator and once these are satisfied, the primary motivator for continuing to lead declaratively moves to be among non-materialist reasons – but, as long as their income is not compromised (purpose of leadership in network marketing). Thirdly, leadership in network marketing fits a spectrum of leadership types depending on the context; and leaders in network marketing use vision to overcome adversity, as well as success to re-iterate the vision (in the context of leadership in network marketing). A further finding was that network marketers use metaphors in two main ways to describe their leadership practice. First, through their metaphors it can be concluded that they refer to themselves as ‘willing overcomers’, and second, they refer to their team members as ‘family’ whilst paradoxically linguistically objectifying them. Towards the end of this study, taking these results into consideration as they are seen by existing leaders in this industry, a portrait of a leader in network marketing is created.
Keywords: Leadership; Network marketing; Multi-level marketing